Physicochemical Properties of Yoghurt Analog from Peanut and Soy Milk - Dewi Kurnianingsih Arum Kusumahastuti; Karina Bianca Lewerissa; Margareta Novian Cahyanti; Sri Hartini; Rifka Dwi Natalia; Yulia Frida Nugrahani (Jurnal Penelitian Pendidikan IPA, 2025)
The global demand for plant-based dairy alternatives is driven by health, environmental, and food allergy or intolerance concerns.  This movement has promoted plant-based yoghurts, which are nutrient-rich and non-dairy. This study examines the physicochemical and sensory characteristics of yogurts made from peanut milk and soy milk, both with and without the presence of filler, a prebiotic polysaccharide. Peanut milk yogurt exhibited a greater fat content of 11.2% wb, protein levels at 6.2% wb, and increased viscosity when compared to soy yogurt. However, soy yogurt exhibited elevated microbial loads (1.5 × 10¹¹ CFU/mL) and protein content when supplemented with inulin, suggesting improved fermentation activity. Both yogurts displayed pH levels appropriate for consumption (4.1–4.6), with peanut milk yogurt demonstrating a marginally higher acidity compared to soy yogurt. The addition of filler had a notable effect on the sensory profile, enhancing texture, taste, and overall acceptability for both peanut milk yogurt and soy yogurt. It is noteworthy that filler-enriched peanut milk yogurt exhibited diminished microbial loads and decreased viscosity, probably as a result of unutilized carbohydrate content and the presence of inhibitory metabolites from fermentation. Proximate analysis indicated that peanut milk yogurt has the potential to function as an effective plant-based yogurt alternative, exhibiting quality comparable to soy yogurt. Organoleptic testing revealed a clear consumer preference for formulations supplemented with inulin, resulting in ratings ranging from "like slightly" to "like extremely." This thorough examination offers significant perspectives on the possibilities of legume-based yogurts in addressing the increasing consumer interest in healthy, plant-derived dairy substitutes